Genetic variability in Peregrine Falcon populations of the Western Palaearctic region - Chiara Mengoni; Inigo Zuberogoitia; Giovanni Boano; Tomas Urban; Enrico guZZo; Nadia Mucci; Maurizio Sara' (Ornis Hungarica, 2019)
We analysed variation in ten polymorphic microsatellite loci and a portion of cytochrome bgeneof mitochondrial DNA in 65 samples from four populations of Peregrine Falcon (Falco peregrinus peregrinus and F. p. brookei) breeding in Northern and Southern Italy, Northern Spain and the Czech Republic to assess genetic diversity in the poorly investigated Western Palearctic region. We added to our cytochrome b sequences a dataset of previously published mtDNA sequences of other populations and subspecies to outline genetic variation in the region on a worldwide basis. Regarding mtDNA we identified 12 haplotypes from our 65 Peregrine Falcon samples, nine of which were new and three already known. The 52% of our samples, including all Italian and Czech specimens, belonged to the previously identified HI haplotype, another 22% of the samples, most of which were from Sicily, showed the new H1 haplotype, while the remaining 26% of the sample partitioned among the other 10 haplotypes. Allelic patterns and genetic structuring of microsatellites were similar to those of other European populations. Genetic differentiation in both mtDNA and microsatellites loci is almost absent and it is not possible to distinguish geographical groups according to taxonomic designation at the subspecies level.